Why Do Students Plagiarise? An empirical study on Built Environment Students Amidst Covid-19 - Afzan, Ahmad Zaini; Julaihi, Wahid; Gui, Hun Chuen; John, Tookey (e-International Publishing House, Ltd., UK, 2023)
Plagiarism has been battering the higher education since the onset of the Covid-19 pandemic. Hence, this research aimed at developing a model which can elucidate the types, reasons and strategies to mitigate plagiarism and misconduct in online examinations. The instrument employed for this research was an online questionnaire, and the study population was determined to be built environment students from five institutions of higher learning. A total of 308 survey forms were analysed using factor analysis, structural equation modelling (SEM) and content analysis. Sixteen (16) case studies were presented and were examined to validate the overall findings.